Parallel processing using Raspberry Pi - Zhou, Lina (2014)
A computer cluster refers to a set of loosely or tightly connected computers that solve computational problems together and in parallel. Raspberry Pi (RPi) Cluster is a set of Raspberry Pi (up to 64) connected to a switch or number of switches and server as a lightweight version of MPI for parallel processing.